Study of gene action for seed yield, oil and quality components in linseed (Linum usitatissimum L.): STUDY OF GENE ACTION FOR SEED YIELD, OIL AND QUALITY COMPONENTS IN LINSEED - ACHILA SINGH; NALINI TEWARI; S D DUBEY (Journal of Oilseeds Research, 2017)
An experiment was conducted to study the gene action of seed yield and quality components in linseed. The analysis of variance showed highly significant differences among the genotypes for all the quality traits. Graphical analysis exhibited non additive gene action playing major role for most of the attributes viz., seed yield per plant, harvest index, moisture content, oil content, protein content of seed, iodine value, palmitic acid, stearic acid and omega-3 content. Components of variance revealed the presence of additive components for oleic acid content and omega-6. Average degree of dominance ( 1/ )0.5 showed over dominance for all the traits except oleic acid contentand omega-6. The value of 2/4 1 indicated asymmetrical distribution of positive and negative genes showing dominance for all the characters. Utilization of biparental mating and recurrent selection schemes which has the virtue of effectively exploiting both additive and non-additive components was suggested for obtaining high yielding genotypes with better quality and high percentage of omega-3 fatty acid.